2018
DOI: 10.2147/hmer.s135337
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for primary biliary cholangitis: current perspectives

Abstract: Primary biliary cholangitis (PBC) is a chronic progressive cholestatic disease characterized by destruction of small- and medium-sized intrahepatic bile ducts. It is no longer a rare disease, since many new asymptomatic cases are incidentally identified. Liver biopsy is diagnostically critical but not always feasible or practical to be performed. Many potential, noninvasive, markers have been proposed to replace liver biopsy and further provide the assessment of disease severity and ultimate prognosis. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 118 publications
1
12
0
Order By: Relevance
“…The co-localization of Sp100 and PML in nuclear dots suggests association of both proteins in multi-subunit complexes. ANAs are a relevant tool for diagnosis of PBC, especially in AMA-negative patients, and their high specificity for PBC has been confirmed in several reports [ 22 , 28 , 29 ]. The existence of anti-Sp100 antibodies in PBC patients was related with a negative course of the disease [ 8 ].…”
Section: Introductionmentioning
confidence: 84%
“…The co-localization of Sp100 and PML in nuclear dots suggests association of both proteins in multi-subunit complexes. ANAs are a relevant tool for diagnosis of PBC, especially in AMA-negative patients, and their high specificity for PBC has been confirmed in several reports [ 22 , 28 , 29 ]. The existence of anti-Sp100 antibodies in PBC patients was related with a negative course of the disease [ 8 ].…”
Section: Introductionmentioning
confidence: 84%
“…However, we found that these scores could not determine early or advanced stage fibrosis. [ 5 , 22 ] Among the studies, sample size, distribution differences for patients according to the fibrosis stage, and variations in the general patient characteristics may affect the diagnostic performance of these non-invasive indicators.…”
Section: Discussionmentioning
confidence: 99%
“…The aspartate aminotransferase (AST)-to-platelet ratio index (APRI), fibrosis index based on four factors (Fib-4), and RDW-to-platelet ratio (RPR) are models that were proposed to detect the fibrosis stage in PBC patients. [ 5 ] In addition, there are models that have no literature data in PBC but that were reported to have a better diagnostic performance in chronic hepatitis B than APRI and Fib-4 scores. One of these models is the S-Index, which is calculated using gamma-glutamyltransferase (GGT) and albumin levels and the platelet count.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Regardless of the differences, both PBC and PSC are progressive diseases and orthotopic liver transplantation (OLT) is eventually required in many patients. (3,4) Despite some recent progress, PSC and PBC still lack reliable noninvasive prognostic biomarkers, (5) hampering the prediction of disease outcomes and assessment of the effect of therapy. (6) To address this unmet need, we have utilized an assay designed to detect liver-speci c circulating cell-free DNA (cfDNA) in plasma as a potential prognostic biomarker for PBC and PSC.…”
Section: Introductionmentioning
confidence: 99%